Implementasi Model Smart Distance Based Pricing pada Aplikasi Pesan Antar Makanan - Widiardiansyah, Azzahid Sidiq Nur; Asriningtias, Yuli (TIN: Terapan Informatika Nusantara, 2025)
Advances in digital technology have changed the way people carry out their daily activities, including ordering and enjoying food. This trend opens up great opportunities for local business actors to adapt through application-based service innovation. Deliboy Delivery Boyolali is a local startup developed to make it easier for people to order food online, as well as support the transformation of delivery services in the Boyolali area. So far, Deliboy's ordering system still depends on the website platform connected to WhatsApp. Although practical, this method often causes obstacles such as improper data recording, time-consuming manual processes, and limitations in determining delivery prices according to distance. Based on this problem, this research offers a solution through the development of an android-based mobile application that integrates three main roles, namely admin, customer, and driver. System development is carried out using the Software Development Life Cycle (SDLC) method through the stages of needs analysis, design, implementation, and testing. The application is developed with the Flutter framework for the user interface, Laravel as the backend server, and MySQL as the database. The testing process applies the Black Box Testing method to ensure the suitability of the functions with the system specifications. The test results showed that all key features, including food ordering, location tracking, digital payments, and a distance-based dynamic pricing system, were working optimally. The implementation of this system has been proven to improve the accuracy of cost calculations, and make it easier for drivers to determine delivery rates automatically based on distance, thus creating a more transparent, effective, and easy-to-use system.